CDM Baseline Construction for Vietnam National Electricity Grid - Tran Minh Tuyen; Axel Michaelowa (Hamburg Institute of International Economics (HWWA), 2004)
For projects under the Clean Development Mechanism (CDM), a baseline has to be set to allow calculation of the greenhouse gas emissions reductions achieved. An important obstacle to CDM project development is the lack of data for baseline definition; often project developers do not have access to data and therefore incur high transaction costs to collect them. The government of Vietnam has set up all necessary institutions for CDM, wants to promote CDM projects and thus is interested to reduce transaction costs. We calculate emission factors of the Vietnam electricity grid according to the rules defined by the CDM Executive Board for small scale projects and for large renewable electricity generation projects. The emission factors lie between 365 and 899 g CO2/kWh depending on the specification. The weighted operating and build margin reaches 600 g for 2003, while grid average reaches 399 g. Using three-year averages, a combined build and operating margin of 705 g is calculated. We hope that these data facilitate CDM project development in the electricity supply and energy efficiency improvement in Vietnam.
Keywords: D62; Q41; Q25; F18; 330; CDM; baseline; electricity generation; Vietnam; Clean Development Mechanism; Elektrizitätswirtschaft; Stromnetz; Luftverunreinigung; Kohlendioxid; Vietnam